Inequity, political violence, and agrarian reform role (2006)
This work tries to add new elements to the debate on relation between income and land inequality and political violence. Here is analyzed the role of land reforms on the relation between inequality and political violence. The methodology implemented is a statistical exercise of panel of data with fixed effects for a set of 31 countries of different continents for the period 1946-1999. The main conclusions are: agrarian reforms still have a great role as instruments for social, economic and political issues, considering the correlation between income and land distribution inequality and political violence. Although agrarian reforms tend to reduce political violence in long term, its capacity is poor due to the limited impact of some land reforms. That situation is a limit for coexistence of democratic political institutions with low levels of political violence. Therefore, the presence of democratic procedures and institutions doesn’t imply a reduction of political violence in high inequality environments.